2016
DOI: 10.1002/ijc.30291
|View full text |Cite
|
Sign up to set email alerts
|

The potential diagnostic value of serum microRNA signature in patients with pancreatic cancer

Abstract: Biomarkers for early diagnosis of patients with pancreatic cancer (PC) are needed. Our aim was to identify panels of miRNAs in serum in combination with CA 19-9 for use in the diagnosis of PC. Four hundred seventeen patients with PC were included prospectively from Denmark (n 5 306) and Germany (n 5 111). Controls included 59 patients with chronic pancreatitis (CP) and 248 healthy subjects (HS). MiRNAs were analyzed in pretreatment serum samples from 3 cohorts: discovery cohort (754 human miRNAs, TaqMan V R Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 42 publications
0
46
0
1
Order By: Relevance
“…The levels of miR-10b, -20a, -21, -30c, -106b, -181a, -483, -20, -let7a, and -122 were assayed in exosomes and plasma, since these miRs have either been implicated in PDAC or in modulation of cancer cell proliferation and migration [2426,3541]. Exosomal miR-10b, -20a, -21, -30c, -106b, and -181a were present at high levels in PDAC and were low in the CP and normal samples, whereas exosomal miR-let7a (which is also known as let7a or let-7a) and miR-122 were lower in PDAC samples by comparison with either normal or CP samples, while miR-483 levels were similar in all three groups (Table 6 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of miR-10b, -20a, -21, -30c, -106b, -181a, -483, -20, -let7a, and -122 were assayed in exosomes and plasma, since these miRs have either been implicated in PDAC or in modulation of cancer cell proliferation and migration [2426,3541]. Exosomal miR-10b, -20a, -21, -30c, -106b, and -181a were present at high levels in PDAC and were low in the CP and normal samples, whereas exosomal miR-let7a (which is also known as let7a or let-7a) and miR-122 were lower in PDAC samples by comparison with either normal or CP samples, while miR-483 levels were similar in all three groups (Table 6 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous miRs are overexpressed in PDAC, including miR-10b, -20a, -21, -30c, -106b, -196a, -196b, -203, -155, -205, -210, -221, -222, -223, -486, -744, and 17-5p [2426,3541]. Some of these miRs are present at high levels in the plasma and serum of patients with PDAC [26,41].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from autoimmune antibodies, other novel markers including serum micro RNAs (miRNAs) signature have been reported to play a role in differentiating pancreatic carcinoma from AIP with high accuracy [26, 27]. MiRNA are endogenous small non-coding RNAs consisting of 19–25 nucleotides, which can interfere with gene transcription and/or translation, thus modulate the targeted gene expression[28].…”
Section: Discussionmentioning
confidence: 99%
“…miR-483), miR-155, miR-21, miR-34 and so on[28]. They not only provide for novel therapeutic options for pancreatic malignancy treatment, also the chance to aid in early diagnosis, disease monitoring and prognostic analysis[27, 29]. Recently, Manabu Akamatsu and his colleagues reported that four MAKP-associated miRNAs, miR-7, miR-34a, miR-181d, and miR-193b can be candidate biomarkers to differentiate pancreatic malignancy from AIP [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation